(untitled) (Journal of the College of Basic Education, 2023)
Numerical simulations of charged analogues of isentropic super-dense star model by using a particular eclectic field, which involves a parameter K have been obtained and the general solution for star is derived for all negative values K. Runge-Kutta method has been used to represent superdense star models with ultrahigh surface density of the order. The physical properties have been studied and analyzed numerically subject to the energy conditions throughout the star and found to be physically acceptable.